2007
DOI: 10.1007/s00018-007-7303-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics in the whole-genome scanning era: Crohn’s disease as example

Abstract: Nutrigenomics has the potential to tailor diets to optimize health, based on knowledge of key genetic polymorphisms. Identification of candidate genes is often based on a priori knowledge of disease processes. However, genome-wide association methods are not only validating previously identified genes and polymorphisms, but also revealing new gene-disease associations not anticipated from prior knowledge. In Crohn's disease (CD), such studies not only confirm the importance of caspase-activated recruitment dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 109 publications
1
10
0
7
Order By: Relevance
“…Many multifunctional zinc finger proteins, such as CTCF, WT1, GLI, ZNF74 and A20, have been linked to human development and disease, usually acting as oncogenic or tumour suppressor proteins [5–8, 32]. Previous studies have shown that ZNF300 is associated with MDS [33] and Crohn’s disease [20]. Our data demonstrate that ZNF300 may promote proliferation by suppressing p21 and p27 and activating NF‐κB and ERK.…”
Section: Discussionmentioning
confidence: 56%
“…Many multifunctional zinc finger proteins, such as CTCF, WT1, GLI, ZNF74 and A20, have been linked to human development and disease, usually acting as oncogenic or tumour suppressor proteins [5–8, 32]. Previous studies have shown that ZNF300 is associated with MDS [33] and Crohn’s disease [20]. Our data demonstrate that ZNF300 may promote proliferation by suppressing p21 and p27 and activating NF‐κB and ERK.…”
Section: Discussionmentioning
confidence: 56%
“…This up-regulation may contribute to the formation of desmoids tumors [7]. ZNF300 is also significantly up-regulated in undifferentiated human embryonic stem cells [2], and is associated with inflammation of the digestive tract [8]. These results indicate that ZNF300 might function as a candidate transcription factor in diverse developmental and pathological processes.…”
Section: Introductionmentioning
confidence: 88%
“…The ZNF300 gene encodes a typical KRAB-type zinc finger protein with twelve C 2 H 2 zinc finger motifs in the C-terminus [6]. Recent studies have shown that ZNF300 plays crucial roles in developmental and pathological pathways [2,7,8]. For example, ZNF300 is abnormally up-regulated in familial adenomatous polyposis-associated desmoids tumours compared to its levels in normal fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…The development of genomics, transcriptomics, proteomics, and metabolomics (Ferguson et al 2007) has given rise to extraordinary opportunities for increasing our understanding about different issues that can be addressed by foodomics. This includes (a) to understand the biochemical, molecular, and cellular mechanisms that underlie the beneficial or adverse effects of certain bioactive food components; (b) to know the identity of genes that are involved in the previous stage to the onset of the disease, and therefore, possible molecular biomarkers (Greenspan 2001); (c) to determine the effect of bioactive food constituents on crucial molecular pathways (Müller and Kersten 2003); (d) to carry out investigation on unintended effects in GM crops (García-Villalba et al 2008, Levandi et al 2008.…”
Section: Foodomics Toolsmentioning
confidence: 99%